A proteomic analyses to assess the effects of chronic exposure of bisphenol a to adult zebrafish (Danio rerio) - Mai, Ngo Thi; Lan Chi, Do Hong; Nga, Le Phi (Academia Journal of Biology, 2017)
Bisphenol A (BPA) is an endocrine-disrupting compound found in the environment as well as in the plastic food containers for human use. Most impact of this compound to animals is acute toxicity to the liver of young individuals, but little is known about chronic toxicity to the adult liver. Here we report that, when adult zebrafish were exposed to various concentration of bisphenol A for 60 days, we have the number of liver protein spots in 2D-PAGE gels was reduced to 15-25%. Protein identification by HPLC-ESI (electron spray ionization) revealed that sixteen 2D-PAGE spots were remarkably altered and majority of them are related to metabolic energy system; e.g., liver basic L-lactate dehydrogenase B-B chain, ATP synthase subunit beta, and intracellular fatty acid-binding proteins. Besides, heat shock protein 60kDa 1 (HSPD1), which is known to associate with inflammation, was over-expressed in fish liver after exposure to 100 µg/l BPA, but not at lower concentrations of BPA. Thus, chronic exposure to environmental BPA may cause liver dysfunctions. Sixteen hepatic proteins identified in this study would be potential biomarkers for chronic BPA toxicity. Citation: Ngo Thi Mai, Do Hong Lan Chi, Le Phi Nga, 2017. A proteomic analyses to assess the effects of chronic exposure of bisphenol a to adult zebrafish (Danio rerio). Tap chi Sinh hoc, 39(3): 333-341. DOI: 10.15625/0866-7160/v39n3.98995. *Corresponding author: lephinga1@hotmail.com, lephinga@hcmut.edu.vn Received 12 December 2016, accepted 20 August 2017